2005
DOI: 10.1002/elps.200410384
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a novel familial catalase mutation (Hungarian type D) and the possible risk of inherited catalase deficiency for diabetes mellitus

Abstract: The enzyme catalase is the main regulator of hydrogen peroxide metabolism. Recent findings suggest that a low concentration of hydrogen peroxide may act as a messenger in some signalling pathways whereas high concentrations are toxic for many cells and cell components. Acatalasemia is a genetically heterogeneous condition with a worldwide distribution. Yet only two Japanese and three Hungarian syndrome-causing mutations have been reported. A large-scale (23 130 subjects) catalase screening program in Hungary y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Similar results with catalase gene mutations and type 2 diabetes were reported in humans, and this risk might be due to peroxide damage of normally catalase-poor pancreatic β cells [30]. Goth reported a proband of type D Hungarian acatalasemia develop type 2 diabetes at a relatively early age [31] and there is higher incidence of diabetes (type 1 and 2) in a catalase deficient family than a normocatalasemic family [5]. The acatalasemic diabetes mice model may reveal the exact mechanisms by which hydroxyl radical affects pancreatic dysfunction and it may lead to the development of new treatments for human diabetes.…”
Section: Accepted Manuscriptsupporting
confidence: 64%
“…Similar results with catalase gene mutations and type 2 diabetes were reported in humans, and this risk might be due to peroxide damage of normally catalase-poor pancreatic β cells [30]. Goth reported a proband of type D Hungarian acatalasemia develop type 2 diabetes at a relatively early age [31] and there is higher incidence of diabetes (type 1 and 2) in a catalase deficient family than a normocatalasemic family [5]. The acatalasemic diabetes mice model may reveal the exact mechanisms by which hydroxyl radical affects pancreatic dysfunction and it may lead to the development of new treatments for human diabetes.…”
Section: Accepted Manuscriptsupporting
confidence: 64%
“…In summary, there is growing evidence that mitochondria and peroxisomes possess an interconnected redox-homeostasis system, which is regulated by yet unknown signaling events. Amazingly, acatalasemia is generally reported as a benign disorder; however, Goth et al (2005) reported an increased incidence of diabetes mellitus in a Hungarian family hypothesizing that an increased ROS production could damage the insulin-producing b-cells of the pancreas. The significance of this assumption has very recently been affirmed in a study which demonstrated that diabetesassociated lipotoxicity was caused by H 2 O 2 -production during peroxisomal b-oxidation, since pancreatic b-cells showed very low levels of catalase expression , thus interconnecting peroxisomal ROS with another age-related disease.…”
Section: Mysterious Signals: Peroxisomes and Reactive Oxygen Speciesmentioning
confidence: 96%
“…Catalase is also an important enzyme in the reactions to reduce superoxide levels, and thereby prevents cell damage [41]. Patients with reduced catalase activity have a higher incidence of oxidative stress-related diseases such as atherosclerosis [42], diabetes [43,44] and dyslipidemia [45]. The last gene in which an association has been found is the thioredoxin gene.…”
Section: Discussionmentioning
confidence: 99%